Adding Value by Taking a National and Institutional Approach to Research Data: The ANDS Experience - David Groenewegen; Andrew Treloar (International Journal of Digital Curation, 2013)
The Australian National Data Service (ANDS) has been working to add value to Australia’s research data environment since 2009. This paper looks at the changes that have occurred over this time, ANDS’ role in those changes and the current state of the Australian research sector at this time, using case studies of selected institutions.